Changes in Mandibular Alveolar Bone Thickness Following All 4s and All 5s Premolar Extraction In Bimaxillary Protrusion Cases: A CBCT Study - Neha Rathore; Rashme Rashme; P. M. Roveena; N. Lingeshkumar; Mariea Francis; S. Vikram (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Bimaxillary protrusion is a common orthodontic condition characterized by excessive forward positioning of both the maxilla and mandible. The treatment often involves premolar and molar extractions to achieve optimal alignment and retraction. Cone-beam computed tomography (CBCT) offers a precise method to evaluate changes in mandibular alveolar bone morphology following such extractions. This study aims to compare the morphological changes in the mandibular alveolar bone following 4-premolar and 5-premolar/molar extractions in patients with bimaxillary protrusion. Materials and Methods: A total of 40 patients with bimaxillary protrusion were selected for this study and divided into two groups: Group A (n = 20) underwent 4-premolar extractions, while Group B (n = 20) underwent 5th premolar/molar extractions. CBCT scans were taken pre-treatment and 12 months post-treatment. Key parameters assessed included alveolar bone height, thickness at different root levels (3 mm, 6 mm, and 9 mm from the cementoenamel junction), and cortical bone thickness. Statistical analysis was performed using paired t-tests and independent t-tests, with a significance level set at P < 0.05. Results: Group A showed a significant reduction in alveolar bone thickness at all root levels, with mean reductions of 1.2 mm (±0.3), 1.5 mm (±0.4), and 1.8 mm (±0.5) at 3 mm, 6 mm, and 9 mm, respectively. Group B demonstrated similar reductions but with slightly higher values: 1.4 mm (±0.4), 1.7 mm (±0.5), and 2.0 mm (±0.6). Alveolar bone height decreased significantly in both groups, with a greater reduction observed in Group B (mean decrease of 2.5 mm versus 1.9 mm in Group A). Cortical bone thickness changes were minimal and statistically insignificant in both groups. Conclusion: Both 4-premolar and 5-premolar/molar extractions lead to significant changes in mandibular alveolar bone morphology. However, 5th premolar/molar extractions result in slightly greater reductions in alveolar bone height and thickness. CBCT provides a reliable method for monitoring these changes, emphasizing the need for careful planning in extraction-based orthodontic treatment.